The East Asian Seas Congress 2003 Regional Implementation of the WSSD Commitments for the Seas of East Asia. - Chua, Thia-Eng; Ross, S.Adrian; Mangahas, Paolo; San, Maria Cecilia (GEF/UNDP/IMO Regional Programme on Building Partnerships in Environmental Management for the Seas of East Asia, 2004)
PEMSEA Workshop Proceedings no. 13